Eye and ocular adnexa manifestations of MED12-related disorders. (2nd January 2022) - Shah, Arth; Bapna, Monika; Al-Saif, Hind; Li, Rachel; Couser, Natario L.
ABSTRACT: Background: MED12 -related disorders are a rare group of intellectual disability syndromes with a broad range of phenotypic characteristics. The phenotypic spectrum of MED12 -related disorders currently includes X-Linked Ohdo Syndrome, Lujan-Fryns Syndrome (LS), and FG syndrome type 1 (FG), also known as Opitz-Kaveggia Syndrome. The MED12 gene encodes the largest component of the mediator complex of RNA polymerase II, which is critical for recruiting activators and repressors to regulate the transcription of genes critical to growth, development, and differentiation. Methods: We performed a systematic literature review of previously published cases to highlight the key ocular features in individuals with MED12 -related disorders. In addition, we present a new case of a female patient with a de novo pathogenic c. 3866A>G, p.Q1289R variant. Ocular manifestations are not uncommon in MED12 -related disorders, but have not been characterized in literature reports. Commonly reoccurring reported eye and ocular adnexa features within the spectrum include ptosis, downslanting palpebral fissures, and hypertelorism. Other less common findings include strabismus, astigmatism, and optic nerve hypoplasia. Results: Our patient presented with developmental delay, mild hypotonia and dysmorphic features including frontal bossing, high arched palate, and syndactyly of the 2 nd and 3 rd toes bilaterally. Discussion: Ocular manifestations identified in this patient included intermittent esotropia, hyperopic astigmatism, epicanthal folds and ptosis bilaterally.